REZEKNES AUGSTSKOLA INFORMATION SYSTEM SERVICE ORIENTED ARCHITECTURE SOLUTION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The goal of this work is to analyze information about main principles of creating information systems using service oriented architecture and create RA integrated information system conceptual model. The proposed system model was developed based on service oriented architecture, with additional description of main principles. Final part contains RA information system service oriented architecture conceptual model with development principles. Using knowledge gathered from analyzes and examinations performed in this work, author gives proposals for integrated information system architecture development principles.